Iron Limitation of a Springtime Bacterial and Phytoplankton Community in the Ross Sea: Implications for Vitamin B12 Nutrition - Bertrand, Erin M.; Saito, Mak A.; Lee, Peter A.; Dunbar, Robert B.; Sedwick, Peter N.; DiTullio, Giacomo R. (Frontiers in Microbiology, 2011)
The Ross Sea is home to some of the largest phytoplankton blooms in the Southern Ocean. Primary production in this system has previously been shown to be iron limited in the summer and periodically iron and vitamin B12 colimited. In this study, we examined trace metal limitation of biological activity in the Ross Sea in the austral spring and considered possible implications for vitamin B12 nutrition. Bottle incubation experiments demonstrated that iron limited phytoplankton growth in the austral spring while B12, cobalt, and zinc did not. This is the first demonstration of iron limitation in a Phaeocystis antarctica-dominated, early season Ross Sea phytoplankton community. The lack of B12 limitation in this location is consistent with previous Ross Sea studies in the austral summer, wherein vitamin additions did not stimulate P. antarctica growth and B12 was limiting only when bacterial abundance was low. Bottle incubation experiments and a bacterial regrowth experiment also revealed that iron addition directly enhanced bacterial growth. B12 uptake measurements in natural water samples and in an iron fertilized bottle incubation demonstrated that bacteria serve not only as a source for vitamin B12, but also as a significant sink, and that iron additions enhanced B12 uptake rates in phytoplankton but not bacteria. Additionally, vitamin uptake rates did not become saturated upon the addition of up to 95 pM B12. A rapid B12 uptake rate was observed after 13 min, which then decreased to a slower constant uptake rate over the next 52 hours. Results from this study highlight the importance of iron availability in limiting early season Ross Sea phytoplankton growth and suggest that rates of vitamin B12 production and consumption may be impacted by iron availability.